Staphylococcus aureus septicemia presenting as disseminated intravascular coagulation - thrombotic thrombocytopenic purpura overlap and thrombus in inferior vena cava, right atrium and right ventricle: a case report - Zafar, Khwaja Saifullah; Singh, P. S.; Raj, Pulak (International Journal of Research in Medical Sciences, 2017)
Staphylococcal sepsis following furunculosis and complicated by suspected deep vein thrombosis and septic inferior vena caval, right atrium, right ventricle emboli accompanied by disseminated intravascular coagulation (DIC) - thrombotic thrombocytopenic overlap in a 65 years old lady is presented. She was managed successfully with antibiotics and anticoagulation. The case is reported for its rarity and brings to light the vivid manifestations of septicemia specially staphylococcal.